Multi-Target Concurrent Vital Sign and Location Detection Using Metamaterial-Integrated Self-Injection-Locked Quadrature Radar Sensor - Yuan, Yichao; Lu, Chunchi; Chen, Austin Ying-Kuang; Tseng, Chao-Hsiung; Wu, Chung-Tse Michael (IEEE transactions on microwave theory and techniques, 2019)
A new architecture of self-injection-locked (SIL) quadrature radar sensor based on a metamaterial (MTM) leaky-wave antenna (LWA) to detect multi-target vital sign and location simultaneously is proposed for the first time. The angular information of targets is obtained by a 1-D MTM LWA with -50° to +30° beam-steering angle when the frequency varies from 1.85 to 2.85 GHz. Furthermore, the distance from the radar sensor to the targets is obtained by imposing the frequency-shift keying (FSK) modulation on the radar waveforms. Meanwhile, the vital sign signals of multiple targets can be extracted from the Doppler frequency spectrum. For the proof of concept, two frequencies, 2.24 and 2.45 GHz, are chosen to detect two targets at different locations, which correspond to the scanning angle at -10° and -40°, respectively. A first-order microwave differentiator followed by a quadrature coupler is employed to convert the radio frequency (RF) signals from the output of the MTM LWA to in-phase (I) and quadrature (Q) RF signals with frequency-dependent amplitudes, thereby eliminating the null point issues for radar detection. Experimental results show that the proposed SIL MTM radar sensor can detect the target location accurately, while the obtained vital sign results agree well with the ground truth.